The Division of Labor: Kelompok Penjahit Pakaian di Amplaz Kota Ambon - Madubun, El-Roi Rizsaldie; Talaperuw, Johanis; Paays, Vitalona C (Jurusan Sosiologi FISIP Universitas Pattimura, 2025)
This study examines the division of labor system used by the clothing tailor group in Amplaz, Ambon City. This study uses qualitative research methods to explain the division of labor in the clothing tailor group in Amplaz. The results of the study found that the division of labor in the tailor group is based on the specialization of sewing skills possessed by the tailors. In the sewing business premises in the Amplaz building, there are sewing businesses owned by the business owner who employs several tailors as employees, and there are also businesses owned by the tailors themselves or private businesses. The clothing tailor group is divided into two: a group of tailors who work for the business owner, and a group of tailors who have their own business. The two groups of tailors have different division of labor systems in the tailor group based on the specialization of sewing skills possessed by the tailors. The division of labor based on the specialization of skills possessed can give rise to solidarity based on dependence on skills to gain profit. This solidarity is rational because it is based on the same goal of gaining profit. The division of labor creates solidarity that can create trust, networks, and norms within the tailor group.